Comparative Evaluation between Atmospheric and Sub-baric processing of Gulabjamun - Basava, Sharana; R, Menon Rekha; Y S, Praveen Kumar; Manjunatha, M; Kumar, G Mahesh; Nath, B S (Indian Journal of Dairy Science, 2019)
Gulabjamun, a popular Indian dairy sweet, is characterised with a brown crust and a soft, slightly spongy core with a uniform granular texture and a pleasant cooked flavour. The sub-baric processing is a novel technology which uses low temperature, low pressure and minimal exposure to oxygen which ultimately improves the quality parameters of fried foods. An attempt was made to compare conventional and sub-baric processed Gulabjamun in terms of its sensory, physical, chemical and microbial attributes. The processing conditions for frying were 118°C/5min/400mmHg vacuum and 140°C/8min/atm for sub-baric frying and conventional frying, respectively. The soaking conditions were 60°Brix at 30°C for 5min for sub-baric soaking and 63°Brix/60°C/4 h for conventional soaking.  The sub-baric frying of Gulabjamun resulted in reduced oil and moisture content in the final product. Microbial enumeration also indicated a lower count in sub-baric fried product when compared to conventionally fried Gulabjamun. The colour of both samples was comparable while the textural properties were found to be better for sub-baric processed product. Sensory score for overall acceptability based on 9 point hedonic scale were 8.2 and 7.14 for sub-baric processed and conventional product, respectively. Apart from these advantages, sub-baric processing recorded significantly less processing time than the conventional method.